Dispersed consumption versus compressed output: Assessing the sectoral effects of a pandemic - Saman Darougheh (Danmarks Nationalbank, 2020)
I process credit-card consumption data through an input-output model of sectoral linkages to impute the sector-level output responses to the Covid-19 pandemic. The sector-level consumption responses are highly dispersed and even positive for some. Yet, all sectors suffer from output losses. Production of intermediate goods stabilizes output. Consequently, the sectoral dispersion of final consumption is larger than sectoral dispersion of output produced.
Keywords: E01; E21; E23; E32; E37; 330; Danish economy: Economic activity and employment; Danish economy: Models